Reconceptualizing Recruitment in Qualitative Research. (1st October 2021) - Bonisteel, Isaac; Shulman, Rayzel; Newhook, Leigh A.; Guttmann, Astrid; Smith, Sharon; Chafe, Roger
Adequate participant recruitment is critical for any qualitative research project. Our research team experienced numerous difficulties when attempting to recruit young adults with type 1 diabetes to discuss their transition from pediatric to adult-focused care. Using our experience as a case study, we identify the activities involved in four phases of participant recruitment: (1) development of a recruitment plan, (2) implementation, (3) participant engagement post-data collection, and (4) post-recruitment assessment. We present a new definition of participant recruitment which better captures the range of activities involved. We discuss aspects impacting recruitment in our case: the influence of other stakeholders, the dynamic nature of recruitment, recruitment of specific populations, and the challenges of recruiting within a healthcare environment. Finally, we identify and consider four factors that impact participant recruitment: communication, participant interest/value, participant trust in the research project, and participant availability and consider potential strategies for overcoming barriers related to each factor. In the end, our case underscores the centrality and potential fluidity of participant recruitment within qualitative research.